2016
DOI: 10.1007/s00381-016-3202-3
|View full text |Cite
|
Sign up to set email alerts
|

Bladder perforation by ventriculoperitoneal shunt

Abstract: Based on this single experience and a literature review, the authors classified the clinical signs and symptoms of bladder perforation by the ventriculoperitoneal shunt catheter. Finally, the authors propose a more conservative approach for this rare complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…In the index case, there were no obstructive symptoms or vesical calculi. It can come out to be visible externally through urethra, which has been reported in 12 patients previously [7][8][9][10][11][12][13][14][15][16][17][18]. This can be asymptomatic as in our case or it can present with urinary symptoms like urinary incontinence [19] or hematuria [20].…”
Section: Discussionsupporting
confidence: 56%
“…In the index case, there were no obstructive symptoms or vesical calculi. It can come out to be visible externally through urethra, which has been reported in 12 patients previously [7][8][9][10][11][12][13][14][15][16][17][18]. This can be asymptomatic as in our case or it can present with urinary symptoms like urinary incontinence [19] or hematuria [20].…”
Section: Discussionsupporting
confidence: 56%
“…So, this complication should be considered in this patient. Regarding diagnosis, it is recommended at least to perform an abdominal ultrasound [2] as we did in our case. Prasad et al [7] suggested that this perforation is caused by a series of events such as catheter fixation, penetration and eventual perforation of the bladder wall, with subsequent exteriorization through the urethra [7,8].…”
Section: Discussionmentioning
confidence: 82%
“…This complication is much more frequent in the pediatric age (67.9%) and there seems to be no gender association or any link with the etiology of hydrocephalus (Table 1). Some authors argue that bladder perforation may be related to a bigger bladder volume [2] as they observed this complication in 8 patients with an augmented bladder (28.6%). Regarding the clinical presentation, 20 patients (71.4%) presented catheter exteriorization through the urethra, approximately half of them being asymptomatic, as occurred in our case.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations